2009
DOI: 10.1159/000235680
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of a Tissue-Engineered Cornea with Porcine Corneal Acellular Matrix as the Scaffold

Abstract: Interest in developing tissue-engineered cornea has increased with the decrease in the supply of donor tissue. The aim of the present study was to investigate the feasibility and method of reconstructing corneal equivalents with porcine corneal acellular matrix as the scaffold in a dynamic culturing system. Applying the detergent Triton X-100 (1%) and a freeze-drying process, porcine corneas were decellularized and prepared as a scaffold, and hematoxylin-eosin staining and scanning electron microscopy showed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 48 publications
1
27
1
1
Order By: Relevance
“…The concentrations of detergents in our study, 0.5% SDS and 1% Triton-X 100, have previously been used to effectively decellularize the cornea (28,(53)(54)(55). The use of detergents and nucleases for decellularization was effective in removing cellular components from the cornea and these results are consistent with other reports (23,53,54,56).…”
supporting
confidence: 91%
“…The concentrations of detergents in our study, 0.5% SDS and 1% Triton-X 100, have previously been used to effectively decellularize the cornea (28,(53)(54)(55). The use of detergents and nucleases for decellularization was effective in removing cellular components from the cornea and these results are consistent with other reports (23,53,54,56).…”
supporting
confidence: 91%
“…25 Although previous works by different groups described the accuracy of nondetergent decellularization agents, such as sodium chloride, 10,12,26 decellularization of a complete animal cornea likely requires the use of more potent decellularization agents (i.e., the most frequently used ionic and nonionic detergents) First, our results revealed that most decellularization protocols were not able to remove a significant percentage of cells from the animal cornea. In contrast with previous works, the efficiency of cell elimination was very poor except for certain specific times and concentrations of SDS, 12,[17][18][19][20][21] suggesting that 0.1% SDS for 48 hours could be efficiently used for whole-cornea decellularization. The low decellularization efficacy of the rest of protocols could be explained by the presence of the SCL surrounding the cornea.…”
Section: Discussioncontrasting
confidence: 69%
“…These agents were selected due to their decellularization power and in agreement with previous reports describing the use of detergents for decellularization of animal corneas or other organs. SDS and Triton X-100 have been widely applied to decellularize corneas, 12,[17][18][19][20][21] and Igepal and BAK were selected for the first time to determine their usefulness for cornea decellularization. Igepal has been previously used for decellularizing heart valves, 22 pericardium, 23 has never been used as a decellularization agent; nonetheless, it is a potent detergent employed as preservative in many drugs, like glaucoma eye drops, which associates high levels of cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…21 In the cornea, decellularized xenograft matrices have been studied primarily for stromal replacement. [22][23][24][25][26][27][28] In this study, we undertook a tissue-engineering approach to evaluate methods for removing cells from human cadaver corneas while maintaining the integrity of the basement membrane and the stromal matrix. The optimized protocol resulted in a decellularized cornea fully capable of supporting the growth and differentiation of human corneal epithelial and stromal cells in vitro.…”
Section: Introductionmentioning
confidence: 99%